Nurse-Led Intervention to Improve Knowledge of Medications in Survivors of Stroke or Transient Ischemic Attack: A Cluster Randomized Controlled Trial - Olaiya, Muideen T.; Cadilhac, Dominique A.; Kim, Joosup; Ung, David; Nelson, Mark R.; Srikanth, Velandai K.; Bladin, Christopher F.; Gerraty, Richard P.; Fitzgerald, Sharyn M.; Phan, Thanh G.; Frayne, Judith; Thrift, Amanda G. (Frontiers in Neurology, 2016)
Introduction: Limited evidence exists on effective interventions to improve knowledge of preventive medications in patients with chronic diseases, such as stroke. We investigated the effectiveness of a nurse-led intervention, where a component was to improve knowledge of prevention medications, in patients with stroke or transient ischemic attack (TIA). Methods: Prospective sub-study of the Shared Team Approach between Nurses and Doctors For Improved Risk Factor Management (STAND FIRM), a randomized controlled trial of risk factor management. We recruited patients aged ≥18 years and hospitalized for stroke/TIA. The intervention comprised an individualized management program, involving nurse-led education, and management plan with medical specialist oversight. The outcome, participants’ knowledge of secondary prevention medications at 12 months, was assessed using questionnaires. A score of ≥5 was considered as good knowledge. Effectiveness of the intervention on knowledge of medications was determined using logistic regression. Results: Between May 2014 and January 2015, 142 consecutive participants from the main trial were included in this sub-study, 64 to usual care and 78 to the intervention (median age 68.9 years, 68% male, and 79% ischemic stroke). In multivariable analyses, we found no significant difference between intervention groups in knowledge of medications. Factors independently associated with good knowledge (score ≥5) at 12 months included higher socio-economic position (OR 4.79, 95% CI 1.76, 13.07), greater functional ability (OR 1.69, 95% CI 1.17, 2.45), being married/living with a partner (OR 3.12, 95% CI 1.10, 8.87), and using instructions on pill bottle/package as an administration aid (OR 4.82, 95% CI 1.76, 13.22). Being aged ≥65 years was associated with poorer knowledge of medications (OR 0.24, 95% CI 0.08, 0.71), while knowledge was worse among those taking three medications (OR 0.15, 95% CI 0.03, 0.66) or ≥4 medications (OR 0.09, 95% CI 0.02, 0.44), when compared to participants taking fewer (≤ 2) prevention medications. Conclusions: There was no evidence that the nurse-led intervention was effective for improving knowledge of secondary prevention medications in patients with stroke/TIA at 12 months. However, older patients and those taking more medications should be particularly targeted for more intensive education.